Fatti, valori e norme. La libertà dell’impersonale in Georges Canguilhem - Vissio, Gabriele (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
This paper aims to expose the relevance of an impersonal element in the philosophical works of Georges Canguilhem before The Normal and the Pathological. In The Normal and Pathological and in other major writings, the impersonal element is given by the “normativity” of living beings. In the works from the 1920s and 1930s we can find the origins of this “impersonal element” and the political meaning Canguilhem has given to it.